Geochemical Characteristics of Limestone of Wonosari-Punung Formation, Gunungkidul Regency, Yogyakarta, Indonesia - Didik Dwi Atmoko; Anastasia Dewi Titisari; Arifudin Idrus (Geological Agency, 2018)
DOI: 10.17014/ijog.5.2.179-197A geochemical study was carried out to determine the geochemical characteristics of limestone in Wonosari-Punung Formation, and to suggest its depositional conditions and the source of rare earth elements. The study was conducted at Ponjong Area, Gunungkidul Regency, Daerah Istimewa Yogyakarta, Indonesia. White limestone which contains more abundant calcite is characterized by the highest CaO concentration. Red limestone which is associated with impure minerals such as siderite, rodochrosite, hematite, and titanite is typified by depleted CaO but higher SiO2, Fe2O3, MnO, and TiO2 concentrations. Grey limestone characterized by depleted CaO and higher MnO contents is considered to be influenced by the presence of impure minerals of manganite (Mn2O3.H2O) and/or pyrolusite (MnO2). Depletion of Sr concentration in the coloured limestone indicates that the diagenetic process increases from the white limestone to the coloured limestone. The process possibly occurred post-deposition of the limestones. The limestones show positive Mn* values (2.46 - 2.95) and authigenic U values (0.89 - 3.38) that suggest an oxidative environment. The Ce/Ce* values (0.57 - 0.80), Eu/Eu* values (1.04 - 1.88), high Y/Ho ratio, and low LaN/YbN ratio are indications that the rare earth elements in the limestones were derived from terrigenous materials. The positive Eu anomaly and enrichment of Cr and Mn of the limestones are indications of hydrothermal fluid activity taking place in the studied area. Based on the geochemical characteristics of the Punung-Wonosari limestones, the depositional environment and the source of rare earth elements of the limestones were therefore influenced by a combination of hydrothermal fluid activity with small amount of terrigenous material input and post depositional diagenetic process.